When elephants fight, it is the grass that suffers: the Russo-Ukrainian conflict and the decentring-recentring conundrum in EU-Africa relations. Issue 3 (3rd April 2023) - Carbone, Maurizio
ABSTRACT: This article argues that to better understand the evolution of EU-Africa relations it is necessary to decentre the EU's external action and concurrently recentre Africa's international agency, while also interrogating the rise of new powers in Africa. Decentring Europe and recentring Africa means challenging the assumptions that Africa needs Europe more than Europe needs Africa and that African states should align with the EU in international settings in defence of the existing global order. By provincializing the EU and engaging extensively with African voices, this article uses the Russo-Ukrainian conflict to unpack key divides between the EU and Africa on whether and how to isolate Russia, explore its consequences for food security in Africa, and expose some contradictions in the EU's energy policy. It concludes that reconstruction in EU-Africa relations means that the EU should make grounded efforts to treat Africa as a true partner, not an afterthought.